Modal Subjectivities : Self-Fashioning in the Italian Madrigal. - McClary, Susan (University of California Press, 2004)
In this boldly innovative book, renowned musicologist Susan McClary presents an illuminating cultural interpretation of the Italian madrigal, one of the most influential repertories of the Renaissance. A genre that sought to produce simulations in sound of complex interiorities, the madrigal introduced into music a vast range of new signifying practices: musical representations of emotions, desire, gender stereotypes, reason, madness, tensions between mind and body, and much more. In doing so, it not only greatly expanded the expressive agendas of European music but also recorded certain assum.